2022
DOI: 10.3390/met12122099
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Friction Stir Welding Parameters on the Weldability of Aluminum Alloys with Similar and Dissimilar Metals: Review

Abstract: The solid-state welding method known as friction stir welding (FSW) bonds two metallic work parts, whether the same or different, by plastically deforming the base metal. The frictional resistance between both metallic workpieces causes them to produce heat, which produces plastic deformation and welds them. However, the weldability and strength of FSW joints mainly depend on the FSW parameters. This review work highlights the previous research work on the FSW parameters and their effects on the weldability an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 174 publications
(293 reference statements)
0
1
0
Order By: Relevance
“…Additionally, the process can be slower than traditional welding methods, which can be a disadvantage in some applications. Many studies conducted in the last fifteen years have studied the FSW of dissimilar Al alloy joints focusing on several aspects such as process optimization, effect of process parameters, microstructure, mechanical properties, and heat treatments [31][32][33][34][35]. The aim of this review is to present that the process parameters influence the properties of a friction stir welded joint between two dissimilar aluminum alloys.…”
Section: Effect Of Process Parametersmentioning
confidence: 99%
“…Additionally, the process can be slower than traditional welding methods, which can be a disadvantage in some applications. Many studies conducted in the last fifteen years have studied the FSW of dissimilar Al alloy joints focusing on several aspects such as process optimization, effect of process parameters, microstructure, mechanical properties, and heat treatments [31][32][33][34][35]. The aim of this review is to present that the process parameters influence the properties of a friction stir welded joint between two dissimilar aluminum alloys.…”
Section: Effect Of Process Parametersmentioning
confidence: 99%
“…Also, Khalafe et al [293] revealed in their review that various artificial intelligence (AI) techniques, including fuzzy logic, artificial neural fuzzy interfacing system (ANFIS), heuristic methods, heuristic algorithms, wavelet methods, machine learning, hybrid systems, and artificial neural networks, facilitate the enhancement of the rate of production with better accuracy for both similar and dissimilar alloys, also including Al ones.…”
Section: Modeling Of the Fsw Processmentioning
confidence: 99%
“…Therefore, it is necessary to further develop the process to understand the mechanisms that involve the weld formation. Previous works have demonstrated the strong influence that the welding parameters and probe geometry have on the typical defect features of the friction stir welded lap joints (hook and cold lap defects) [9][10][11]. Moreover, it is of paramount importance to consider the effect that other manufacturing variables, such as sealant application or surface treatment, can have on the mechanical performance and manufacturability of the joints.…”
Section: Introductionmentioning
confidence: 99%